INTERNALISASI NILAI-NILAI PANCASILA DALAM KEGIATAN EKSTRA KURIKULER - Tafonao, Hedrianus (Universitas Nias Raya, 2024)
Pancasila is the evolution of the noble principles adhered to by the Indonesian people which are universally recognized and become the basis for all other sources. Chosen by non-Western countries or nations, Pancasila is the paradigmatic direction of science, especially the social sciences. Because non-Western countries have different histories, cultures, and ways of life, they must engage with contemporary science. Ranto stated that (2012:1).